2005
DOI: 10.1002/cncr.21587
|View full text |Cite
|
Sign up to set email alerts
|

Similar response rates and superior early progression‐free survival with gemcitabine, dexamethasone, and cisplatin salvage therapy compared with carmustine, etoposide, cytarabine, and melphalan salvage therapy prior to autologous stem cell transplantation for recurrent or refractory Hodgkin lymphoma

Abstract: The role of fine needle aspiration (FNA) as a first‐line diagnostic modality is well‐established for neoplastic and nonneoplastic liver masses in adults. However, cytopathologic analysis of such lesions in children and adolescents has not been well studied. An 18‐year retrospective review of the cytopathology archives at The Johns Hopkins Hospital identified 44 cases of hepatic FNA in children and adolescents (i.e., 21 years and younger). The cytopathologic material was reviewed and correlated with subsequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 60 publications
1
57
0
5
Order By: Relevance
“…The majority of patients in the study received mini-BEAM 18 or, more recently, GDP based on our institutional data. 35 The role and timing of consolidative radiotherapy peri-ASCT has not been tested in controlled trials. Historically pre-ASCT consolidative radiation has been a source of concern because of potentially high rates of pulmonary toxicity if mediastinal radiation is required.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients in the study received mini-BEAM 18 or, more recently, GDP based on our institutional data. 35 The role and timing of consolidative radiotherapy peri-ASCT has not been tested in controlled trials. Historically pre-ASCT consolidative radiation has been a source of concern because of potentially high rates of pulmonary toxicity if mediastinal radiation is required.…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of previous reports on high-dose chemotherapy, data on CD34 + cell mobilization are lacking and details on PBSC mobilization and collection are reported in a limited number of studies 11,23,[30][31][32] (Table 6). An adequate stem cell collection (>2×10 6 CD34 + cells/kg) was observed in over 80% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies reported data relating to which standard-dose salvage regimen is the best to induce a good clinical response and shrinkage of bulky disease [16][17][18][19][20][21][22][23][24][25] before high-dose therapy. Hence, the identification of new active regimens, combining therapeutic activity and CD34 + stem cell mobilizing potential, is of the utmost importance to increase pre-transplant response rates and, possibly, the final outcome.…”
Section: 4-5 13-15mentioning
confidence: 99%
“…Thus etoposide with high-dose cytarabine and cisplatinum -ESHAP, ICE, mini-BCNU or etoposide, cytosine arabinoside, and melphalan -BEAM, have been used. Recently gemcitabine-containing regimens have shown high response rates with an acceptable side-effect profile [72] and [73].…”
Section: Relapsementioning
confidence: 99%